COMPARISON OF ERYTHROGRAM PROFILES BETWEEN DUTCH WARMBLOOD AND SUMBAWA HORSES AT THE TURANGGA UNIT, SAMAPTA DIRECTORATE, BALI REGIONAL POLICE - Sang Ayu Putu Aura Setyaningsih; Nyoman Sadra Dharmawan; Ida Bagus Oka Winaya (Buletin Veteriner Udayana, 2026)
This study aimed to compare erythrocyte count, hemoglobin concentration, hematocrit value, and erythrocyte indices (MCV, MCH, and MCHC) between Dutch Warmblood horses and local Sumbawa horses maintained at the Directorate of Samapta, Bali Regional Police. The study involved six male horses aged 12–21 years, consisting of three Dutch Warmblood horses and three Sumbawa horses. Blood samples were collected from the jugular vein and analyzed using a Rayto RT 7.600 for Vet hematology analyzer. Blood smear examinations with Giemsa staining were also performed to observe erythrocyte morphology microscopically. Data were analyzed descriptively by comparing the results with reference values for equine hematology. The results showed that erythrocyte, hemoglobin, hematocrit, and erythrocyte indices in both horse breeds were within normal ranges. Dutch Warmblood horses tended to show greater variation in erythrocyte and erythrocyte index values, while Sumbawa horses demonstrated more stable values. Microscopic observations revealed normal biconcave disc- shaped erythrocytes without pathological abnormalities in both breeds. The observed differences in hematological profiles were associated with breed-related physiological adaptations.